Impact of Compression Force on Mechanical, Textural, Release and Chewing Perception Properties of Compressible Medicated Chewing Gums - Yuliia Maslii (MDPI AG, 2021)
Medicated chewing gums (MCGs) represent a beneficial platform for realizing drugs intended for dental prophylaxis and treatment. The present study aimed to investigate the impact of compression force on the mechanical, textural, release, and chewing perception characteristics of compressible MCGs with the combination of lysozyme hydrochloride (LH) and ascorbic acid (AsA). Four batches of MCGs were obtained on a laboratory single-punch tablet machine applying different forces, i.e., 5, 7, 10, and 15 kN, and evaluated by their geometrical parameters, mechanical resistance, surface and internal structure characteristics, texture profile, release behavior, and perception attributes during mastication. It was found that increasing compression force slightly affected resistance to crushing and friability of MCGs, but resulted in surface smoothing and formation of a thicker layer with highly compacted particle arrangement. According to the texture analysis, increasing compression force led to harder and more adhesive gums, indicating possible difficulties in chewing and, therefore, impairment of their consumer properties. Lower compression forces were also found to be preferable in terms of better drug release from the obtained chewing gums. The volunteers’ assessment showed that an increase of compression force led to significantly raising the initial hardness and crumbliness as well as to decreasing the rate of the integral gum mass formation during mastication, which may negatively affect perceptive sensations when using MCGs. Based on the results obtained, the optimal compressing force was selected to be 7 kN, which allows obtaining MCGs with good organoleptic, mechanical, textural, and release properties.